Seroprevalence of Toxoplasma gondii in free-ranging and feral cats on Amami Oshima Island, Japan - MATSUU, Aya; YOKOTA, Shin-ichi; ITO, Keiko; MASATANI, Tatsunori (Journal of Veterinary Medical Science, 2017)
On Amami Oshima Island, free-ranging and feral cats are harmful to wildlife populations. In this study, the seroprevalence of Toxoplasma gondii in these cats was examined using a newly developed Gaussia luciferase immunoprecipitation system assay. Of 1,363 cats, 123 cats (9.0%) was positive for T. gondii. The prevalence was significantly different in different areas; among cats in the rural area, where many wild animals live, including endangered species, T. gondii infection was more prevalent than in the urban area of the island. This finding indicates a possible risk to wildlife of infection from free-ranging and feral cats. Therefore, management of cats is important for wildlife conservation.